ECOTOURISM DEVELOPMENT STRATEGY AT TAMAN WISATA ALAM GUNUNG TUNAK, CENTRAL LOMBOK - Rumba, Rumba; Rahmawati R.A, (Journal of Innovation Research and Knowledge, 2024)
Due to its high biodiversity, TWA Gunung Tunak is susceptible to disturbance. In order to develop as an ecotourism destination, management must implement proper sustainable measures due to the limited supply of natural resources. Descriptive qualitative methods are used in data analysis procedures, such as participant observation, in-depth interviews, and document analysis. This approach places a strong emphasis on in-depth knowledge in order to support the creation of guidelines and procedures for the growth of ecotourism destinations. Human resources, destination management, environmental sustainability, sanitation, security, and comfort are just a few of the barriers that may stand in the way. The following strategies are implemented in order to develop potential and find solutions to these obstacles: weakness-opportunity (W-O) strategies with tourism destination promotion strategies and security and comfort improvement strategies; weakness-threat (W-T) strategies with human resource development strategies and institutional development and destination management strategies; strength-opportunity (S-O) strategies with tourism destination development strategies and tourist attraction development strategies; strength-threat (S-T) strategies with environmental quality improvement strategies and ecotourism tourism development strategies. In summary, there is a great deal of potential for the development of TWA Gunung Tunak as an ecotourism destination. This potential encompasses socio-cultural elements like local knowledge and the warmth of the locals, as well as natural elements like the scenic beauty of the mountains, beaches, and woods.